2017
DOI: 10.1186/s12859-017-1831-5
|View full text |Cite
|
Sign up to set email alerts
|

SimBA: A methodology and tools for evaluating the performance of RNA-Seq bioinformatic pipelines

Abstract: BackgroundThe evolution of next-generation sequencing (NGS) technologies has led to increased focus on RNA-Seq. Many bioinformatic tools have been developed for RNA-Seq analysis, each with unique performance characteristics and configuration parameters. Users face an increasingly complex task in understanding which bioinformatic tools are best for their specific needs and how they should be configured. In order to provide some answers to these questions, we investigate the performance of leading bioinformatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The correctness of alignment programs are crucial to the accuracy of the downstream analyses. Unfortunately, previous studies have shown that while these tools have low false positive rates, they do not necessarily have low false negative rates [3,1]. This means that while many of the reads were likely to be correctly aligned, there are still many incorrectly unaligned reads which should have been aligned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correctness of alignment programs are crucial to the accuracy of the downstream analyses. Unfortunately, previous studies have shown that while these tools have low false positive rates, they do not necessarily have low false negative rates [3,1]. This means that while many of the reads were likely to be correctly aligned, there are still many incorrectly unaligned reads which should have been aligned.…”
Section: Introductionmentioning
confidence: 99%
“…This means that while many of the reads were likely to be correctly aligned, there are still many incorrectly unaligned reads which should have been aligned. These incorrectly unaligned reads, or false negative non-alignments, adversely affect the accuracy of the alignment produced and can also affect the result of downstream analyses, such as variant calling, indel (insertion-deletion) detection and gene fusion detection [1].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the programs described for such a simulation of mutations are SIM-CT ( Audoux et al , 2017 ), SVsim ( https://github.com/GregoryFaust/SVsim ), shuffleseq ( http://emboss.sourceforge.net/apps/release/6.2/emboss/apps/shuffleseq.html ), simuG ( Yue and Liti, 2019 ) and Simulome ( Price and Gibas, 2017 ). Compared to Mutation-Simulator, these tools are either limited in the type of genomes they can operate on (Simulome), limited in their field of use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The correctness of alignment programs are crucial to the accuracy of the downstream analyses. Unfortunately, previous studies have shown that while these tools have low false positive rates, they do not necessarily have low false negative rates 8,9 . This means that while many of the reads were likely to be correctly aligned, there are still many incorrectly unaligned reads which should have been aligned.…”
Section: Introductionmentioning
confidence: 99%
“…This means that while many of the reads were likely to be correctly aligned, there are still many incorrectly unaligned reads which should have been aligned. These incorrectly unaligned reads, or false negative non-alignments, adversely affect the accuracy of the alignment produced and can also affect the result of downstream analyses, such as variant calling, indel (insertion-deletion) detection and gene fusion detection 9 .…”
Section: Introductionmentioning
confidence: 99%